2007
DOI: 10.1073/pnas.0701743104
|View full text |Cite
|
Sign up to set email alerts
|

Terminally differentiated muscle cells are defective in base excision DNA repair and hypersensitive to oxygen injury

Abstract: The differentiation of skeletal myoblasts is characterized by permanent withdrawal from the cell cycle and fusion into multinucleated myotubes. Muscle cell survival is critically dependent on the ability of cells to respond to oxidative stress. Base excision repair (BER) is the main repair mechanism of oxidative DNA damage. In this study, we compared the levels of endogenous oxidative DNA damage and BER capacity of mouse proliferating myoblasts and their differentiated counterpart, the myotubes. Changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 27 publications
6
89
0
Order By: Relevance
“…Values are natural log transformations of data from Tables 1 and 4 in brain and liver. Our measurements in these tissues will disproportionately reflect the activities of highly differ- Narciso et al (2007) demonstrated that a significant reduction in BER capacity occurs during differentiation of actively mitotic skeletal muscle progenitors (myoblasts) to post-mitotic myotubes (myofiber-like). Other authors have shown that BER enzyme activities are upregulated at specific times during the cell cycle (Chaudhry 2007) and are generally elevated in tissues containing higher proportions of actively mitotic cells (see Karahalil et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Values are natural log transformations of data from Tables 1 and 4 in brain and liver. Our measurements in these tissues will disproportionately reflect the activities of highly differ- Narciso et al (2007) demonstrated that a significant reduction in BER capacity occurs during differentiation of actively mitotic skeletal muscle progenitors (myoblasts) to post-mitotic myotubes (myofiber-like). Other authors have shown that BER enzyme activities are upregulated at specific times during the cell cycle (Chaudhry 2007) and are generally elevated in tissues containing higher proportions of actively mitotic cells (see Karahalil et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased BER capacity of terminally differentiated muscle cells has been shown to lead to accumulation of DNA sSSBs upon oxidative stress. 3 As shown in Figure 1a, DNA SSB also accumulate after exposure to an alkylating agent, namely methyl methanesulfonate (MMS; 1 mM, 30 min), which induces SSB as intermediates during the BER process. To gain insights into the fate of persistent SSB in the genome of post-mitotic muscle cells, cell survival was measured in proliferating and terminally differentiated cells following exposure to MMS and CPT by counting metabolically active cells.…”
Section: Resultsmentioning
confidence: 99%
“…DNA repair is strongly affected by the exit from the cell cycle as revealed by downregulation of the major DNA repair pathways. 2 This occurs during differentiation-associated gene reprogramming at transcriptional level as in the case of genes coding for proteins shared by DNA repair and replication (e.g., replicative DNA polymerases, Flap structure-specific endonuclease 1, proliferating cell nuclear antigen and DNA ligase 1) 3 or repair proteins that are cell-cycle related (e.g., XRCC1 (X-ray repair complementing defective repair in Chinese hamster cells 1), uracil-DNA glycosylase). 4,5 Alternatively, post-translational modifications may modify the efficiency of specific DNA repair components as in the case of transcription factor II H that, because of reduced ubiquitination, may lead to decreased global genomic nucleotide excision repair typical of differentiated cells.…”
mentioning
confidence: 99%
“…Differentiated myocytes can efficiently activate p53 after DNA damage but these cells possess a downstream blockade of p53-mediated apoptosis and thus evade death (12). Although seminal studies are emerging on DDR and DNA repair mechanisms in differentiated skeletal muscle cells (10)(11)(12)(13), there is limited knowledge on whether myopathy-causing gene mutations can alter DDR and DNA repair mechanisms in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%